Comparative Hemodynamic Stability in Low-Dose versus Conventional-Dose Bupivacaine for Spinal Anaesthesia in Elderly Patients - Dr. Arvind Patel; Dr. Arvind Patel; Dr Adarsh Kumar Yadav; Dr. Pankaj Singh Patel; Dr. Rashmi Kumari; Dr. Deepesh (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Spinal anaesthesia is favoured for lower-limb and lower-abdominal surgery in the elderly, yet conventional doses of hyperbaric bupivacaine frequently precipitate hypotension and bradycardia. Reducing the intrathecal dose may mitigate these effects while preserving surgical anaesthesia. Methods: In this prospective, randomised, double-blind trial we enrolled 120 patients aged ≥ 65 years (ASA II–III) scheduled for elective hip or knee arthroplasty. Participants received either low-dose (LD, 6 mg) or conventional-dose (CD, 12 mg) 0.5 % hyperbaric bupivacaine with 25 µg fentanyl. Primary outcome was incidence of clinically significant hypotension (≥ 20 % fall in mean arterial pressure or MAP < 65 mmHg) during the first 30 min after block. Secondary outcomes included bradycardia (HR < 50 beats•min⁻¹), vasopressor usage, sensory-motor block characteristics, surgeon satisfaction, and major adverse events. Results: Baseline characteristics were comparable. Clinically significant hypotension occurred in 17 % of LD versus 48 % of CD patients (relative risk 0.35; p < 0.001). Mean MAP at 5, 10, 20 and 30 min was consistently higher in LD (84 ± 9, 82 ± 8, 80 ± 7, 79 ± 6 mmHg) than CD (72 ± 11, 70 ± 10, 68 ± 9, 67 ± 8 mmHg; p < 0.01 at all points). Bradycardia was less frequent in LD (10 % vs 28 %; p = 0.02). Ephedrine requirements (median 0 mg [IQR 0–6] vs 12 mg [6–18]; p < 0.001) and atropine administration (2 % vs 12 %; p = 0.04) were reduced in LD. Surgical anaesthesia was adequate in both groups; time to two-segment regression was shorter in LD (78 ± 14 min vs 103 ± 18 min; p < 0.001) but did not prolong recovery room discharge. No patient required conversion to general anaesthesia. Conclusion: In elderly patients, intrathecal low-dose 0.5 % bupivacaine (6 mg) supplemented with fentanyl provides satisfactory surgical conditions while significantly improving haemodynamic stability compared with the conventional 12 mg dose. Routine dose reduction should be considered to diminish peri-operative cardiovascular morbidity in this population.